Microbiological and molecular aspects of periodontitis pathogenesis: an infection-induced inflammatory condition - Mina Yekani; Mina Yekani; Masoumeh Dastgir; Samaneh Fattahi; Samaneh Fattahi; Shahriar Shahi; Solmaz Maleki Dizaj; Mohammad Yousef Memar (Frontiers in Cellular and Infection Microbiology)
Periodontitis (PD) is the most common oral infectious disease. The primary etiologic cause of the onset and development of PD is dental plaque, which consists of bacterial biofilm domiciled within a complex extracellular mass. In PD patients, there is a progressive breakdown of the periodontal ligament and the alveolar bone. In more advanced stages, tooth loss occurs. The progression of this chronic inflammatory disease involves interactions among numerous microbial pathogens particularly, bacteria, the host’s immune factors, and various environmental factors. Due to persistent infection by periodonto-pathogenic bacteria, there is an impairment of both innate and acquired immunity, leading to tissue destruction. Chronic inflammation in PD may be associated with several systemic diseases, including cardiovascular conditions, respiratory issues, diabetes, neurological diseases, cancer, and adverse pregnancy outcomes. Antibiotic treatment is one of the effective strategies for treating PD cases, although the emergence of some resistant strains may limit the effectiveness some antibiotics. In this review study, we discussed the main bacteria in PD, the interaction with the immune response, the pathogenesis of bacteria in PD and antibiotic treatment. We also outlined the emergence of resistance to antibiotics among these pathogens.